2021
DOI: 10.1111/jocn.15777
|View full text |Cite
|
Sign up to set email alerts
|

‘It was quite a shock’: A qualitative study of the impact of organisational and personal factors on newly qualified nurses' experiences

Abstract: Aims and objectives To explore how newly qualified nurses’ work experiences are constructed through the interplay between self, workplace and home‐life influencing their retention. Background Nurses are critical to achieving the goal of universal health coverage. However, shortages of nursing staff are endemic. Of particular concern, newly qualified nurses are more likely to leave the nursing workforce. The point of transition to working as a newly qualified nurse is a time of vulnerability. Most studies attem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 56 publications
2
41
1
Order By: Relevance
“…Caring obligations were critically important to the nurses but were hampered by night shifts, long working hours and reduced vacation opportunities. The findings are in line with previous studies that found that caregiving responsibilities, inflexible shift schedules, long work hours, rotational shifts and loss of vacation time contributed to low QWL among nurses [8] , [13] , [14] . As reported in a preceding work, these factors alter the balance between work and family life, trigger a sense of inadequacy and guilt toward their dependents and hospitals and compel nurses to juggle managing their children, house and self-needs [15] , [16] .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Caring obligations were critically important to the nurses but were hampered by night shifts, long working hours and reduced vacation opportunities. The findings are in line with previous studies that found that caregiving responsibilities, inflexible shift schedules, long work hours, rotational shifts and loss of vacation time contributed to low QWL among nurses [8] , [13] , [14] . As reported in a preceding work, these factors alter the balance between work and family life, trigger a sense of inadequacy and guilt toward their dependents and hospitals and compel nurses to juggle managing their children, house and self-needs [15] , [16] .…”
Section: Discussionsupporting
confidence: 92%
“…Work context embodies the practice settings in which nurses work and the impact of the work environment on both nurse and patient systems, including management patterns, style of supervision, resource availability, co-worker relationships, promotional opportunities, feedback and a conducive working environment [5] . Helpfulness and assistance from colleagues were associated with a high quality of nursing work life [13] , [28] , [29] . Nonetheless, blame culture [30] , a lack of sufficient resources [6] , [11] , [18] , [21] , [22] , [29] , [31] , a lack of supportive organizational leadership and policies [3] , [20] , [21] , [28] , [32] , a lack of support from the nursing supervisor [3] , [21] , [31] , medical dominance [6] , [31] , a lack of participatory decision-making [6] , [20] , [32] , a lack of promotion [3] , [32] , few professional training opportunities [32] , a lack of personal protective equipment [19] , [20] , [29] and an unsafe environment [28] , [31] contributed to a low QWL among nurses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence from available literature calls attention to the influence of workplace culture on transition experiences and retention of nurses during their initial years of practice (Hazelton et al, 2011;Ho et al, 2021;Wright et al, 2011). Australian action research on new graduate mental health nurses (Hazelton et al, 2011) Karlowicz and Ternus (2009) also recommended that mentorship programmes for novice nurses assist in team-building and improve retention.…”
Section: Workplace Culturementioning
confidence: 99%